2019
DOI: 10.1186/s13052-019-0613-2
|View full text |Cite
|
Sign up to set email alerts
|

The association of prenatal and postnatal macrolide exposure with subsequent development of infantile hypertrophic pyloric stenosis: a systematic review and meta-analysis

Abstract: BackgroundThe association between macrolides use and subsequent occurrence of infantile hypertrophic pyloric stenosis (IHPS) is still debatable. The aim of this study was to conduct a systematic review and meta-analysis of the association between perinatal exposure to macrolides, mainly erythromycin, and the development of pyloric stenosis.MethodsOriginal studies were identified using MEDLINE, Web of Science, Scopus, Google Scholar, and the Cochrane Library databases. Studies investigating the association betw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 37 publications
0
8
0
2
Order By: Relevance
“…Pregnancy is a stage in female life where various physiological changes occur, and it results in a number of risks in relation to pharmacokinetics of different therapeutics [220,221]. The use of some medicines, including antibiotics, may also pose a risk to developing fetus [222,223]. Therefore, the use of phage therapy, which is generally considered safer than the use of antibiotics and lacking serious side effects, may be an attractive alternative for treating uterine infections as well as other diseases during pregnancy [216].…”
Section: Bacteriophages In Female Reproductive System and Pregnancymentioning
confidence: 99%
“…Pregnancy is a stage in female life where various physiological changes occur, and it results in a number of risks in relation to pharmacokinetics of different therapeutics [220,221]. The use of some medicines, including antibiotics, may also pose a risk to developing fetus [222,223]. Therefore, the use of phage therapy, which is generally considered safer than the use of antibiotics and lacking serious side effects, may be an attractive alternative for treating uterine infections as well as other diseases during pregnancy [216].…”
Section: Bacteriophages In Female Reproductive System and Pregnancymentioning
confidence: 99%
“…In 2019, two separate systematic reviews and meta-analyses evaluated the association of prenatal and postnatal macrolide exposure with subsequent development of IHPS. In the first review, Abdellatif et al [ 83 ] found no significant association between macrolide use during pregnancy and development of IHPS, while the evidence on the effects of prenatal macrolide exposure was not conclusive in the second review [ 84 ].…”
Section: Use Of Azithromycin In Pregnancy and Adverse Offspring Outcomesmentioning
confidence: 99%
“…Ha demostrado tener una fuerte agregación familiar. Los hermanos de pacientes con EHP tienen de 15 a 30 veces más riesgo de padecer esta enfermedad y afecta al 50% de los gemelos idénticos (8). Se ha sugerido en términos generales una herencia autosómica, pero no hay un gen específico identificado que sea responsable de dicha enfermedad (9).…”
Section: Factores Genéticosunclassified
“…Un factor de riesgo ambiental sospechado es la exposición a macrólidos, principalmente a la eritromicina, en la etapa prenatal. Sin embargo, la evidencia que respalda esta asociación sigue siendo elusiva (5,8). Además, se ha observado también una relación con la exposición prenatal a Talidomida, Hidantoina, Trimetadiona, pesticidas agrícolas y a la administración de fórmulas lácteas hiperosmolares (9).…”
Section: Factores Extrínsecosunclassified